Diffuse Idiopathic Skeletal Hyperostosis: Persistent Sore Throat and Dysphagia in an Elderly Smoker Male. (14th September 2017) - Goico-Alburquerque, Ana; Zulfiqar, Beenish; Antoine, Ranae; Samee, Mohammed
Abstract : Diffuse idiopathic skeletal hyperostosis (DISH) is rarely symptomatic. However, it can present with dyspnea, hoarseness, dysphagia, and stridor. An 80-year-old chronic smoker male presented with 6-month history of sore throat and progressive dysphagia. Computed tomography of the neck revealed bulky anterior bridging syndesmophytes along the anterior aspect of the cervical spine and facet effusion involving four contiguous vertebrae consistent with DISH. Dysphagia secondary to DISH was diagnosed. Fiberoptic laryngoscopy showed bilateral vocal cord paralysis. Patient's airway became compromised requiring tracheostomy tube placement. After discussion of therapeutic options, patient agreed on a percutaneous endoscopic gastrostomy tube insertion for nutritional support. Osteophytectomy was left to be discussed further.